THE EFFECT OF CONSUMPTION OF BANANA BLOSSOM ON INCREASING PRODUCTION OF BREAST MILK IN POST PARTUM MOTHERS IN THE WORKING AREA OF SIBONGBONG SUBDISTRICT COMMUNITY HEALTH CENTERS YEAR 2022 - Hasibuan, Nurhayati; Nasution, Elliyana (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Breast milk contains various important substances needed for the growth and development of the baby. The purpose of this study was to determine the effect of banana heart consumption on increasing breast milk production in nifah mothers before and after consuming banana heart in the Sibongbong Simarpinggan Health Centre Working Area. This type of research is quasi experimental with one group pretest-posttest design. Based on the data obtained and tested using paired sample test statistics obtained p = 0.02 <0.005. This shows that there is an effect of giving banana heart to the quality of breast milk of mothers, therefore it is recommended for health workers to knowledge of mothers who breastfeed with efforts to increase breast milk production with foods that are easily accessible.